Pharmacokinetics of solifenacin in pediatric populations with overactive bladder or neurogenic detrusor overactivity - Stacey Tannenbaum; Martin den Adel; Walter Krauwinkel; John Meijer; Adriana Hollestein‐Havelaar; Frank Verheggen; Donald Newgreen (Pharmacology Research & Perspectives, 2020)
Abstract The aim of this investigation was to characterize and compare the pharmacokinetics (PK) of the antimuscarinic drug solifenacin in pediatric patients with overactive bladder (OAB) or neurogenic detrusor overactivity (NDO) utilizing data from three phase III trials. LION was a placebo‐controlled, 12‐week trial in children (5–<12 years) and adolescents (12–<18 years) with OAB. MONKEY and MARMOSET were open‐label, 52‐week trials in children and adolescents or younger children (6 months–<5 years), respectively, with NDO. During the trials, solifenacin doses could be titrated to weight‐adjusted pediatric equivalent doses (PEDs) of 2.5, 5, 7.5, or 10 mg day–1. Nonlinear mixed effects modeling was used to develop population PK models to characterize the PK in patients with either OAB or NDO. Overall, 194 children and adolescents received solifenacin. At the time of PK sampling, the majority (119/164 [72.6%] patients) were receiving PED10 once daily. All population models included first‐order oral absorption, a lag time, and interindividual variability. PK analysis showed that apparent clearance was similar in both patient populations. Mean apparent oral plasma clearance (CL/F), apparent volume of distribution during the terminal phase (Vz/F), and terminal half‐life (t1/2) were higher in adolescents than in children, but median time to maximum plasma concentration (tmax) was similar. Dose‐normalized exposure results were similar for both younger and older patients with OAB or NDO. In conclusion, population PK modeling was used to successfully characterize solifenacin PK in pediatric patients with OAB or NDO. Similar solifenacin PK characteristics were observed in both populations.